MICROSOFT ACCESS APPLICATION SUPPORT SERVICES AS A DISTRIBUTOR INFORMATION IN PT. LAKSANA SUKSES MANDIRI - Meyske Aferta; Ir. Fitri Sjafrina. MM (Jurnal Sistem Informasi, 2003)
Technology continues to advance in all the amendments, along with the developmentof the business world working in various industrial fields. Information servicesrelating to a presentation of information services. In this study, the authors make a listof stocks to help service personnel in carrying out daily activities and also assistsofficers in making a report to the leadership.At the time of check list items in order of PT. LSM care workers should pay attentionto all the codes in the service with the existing code of goods in warehouse, afterchecking the existing data warehouse, the officers will be checking back again withall the codes from the list of customer orders.To make a presentation of the information service distributors in making informationservices sales and inventory in PT. LSM authors use the application programMicrosoft Access 1997 version.Information services of the company still uses big books that have faced severalobstacles, the computer as supporting information services can be used as tools tosolve problems and may make a presentation of useful information for anyone whoneeds care workers in particular, its customers and is also head of the company .